Challenges and new strategies for Gulf War illness research - Henry H. Q. Heng (Wolters Kluwer Medknow Publications, 2016)
Gulf War illness (GWI) research has generated an abundance of interesting but diverse data. While increased molecular mechanisms have been identified, the high levels of heterogeneity for initial trigger factors, cellular defects, and symptoms continuously challenge the efforts of clinical implications of the research, including the search for biomarkers and the common mechanism of GWI. In this analysis, I consider GWI as an adaptive illness condition where system stresses and genome instability-mediated cellular evolution play an important role. By further defining GWI as an environmental illness caused by extremely high levels of specific Gulf War (GW) stresses, the challenges for GWI research are briefly reviewed, with comparisons to other common and complex diseases such as cancer. Based on the new discovery that many GWI patients display elevated genome instability coupled with increased cellular stress, a general model of GWI is proposed to unify GW-specific stress, cellular damage, and genome-heterogeneity-mediated cellular adaptation and evolution, as well as diverse-related symptoms. Finally, some new strategies are suggested based on the general model of GWI.